A label-free and selective SERS-based sensor for determination of ampicillin contamination in water using a fabric gold–silver alloy substrate with a handheld Raman spectrometer. (13th January 2023) - Karn-orachai, Kullavadee; Ngamaroonchote, Aroonsri
Abstract : A plasmonic Au–Ag alloy fabric substrate is developed via in situ self-assembly of Au–Ag alloy NPs on muslin fabric. An appropriate molar ratio of Au and Ag and type of substrate are proved to be key factors for selective detection of ampicillin. Abstract : A flexible and low-cost surface-enhanced Raman scattering (SERS) substrate was developed and coupled with a handheld Raman spectrometer for fast screening and label-free ampicillin detection. To generate a strong electromagnetic field SERS substrate, in situ self-assembly of gold–silver alloy nanoparticles (Au–Ag alloy NPs) on muslin fabric was carried out via a chemical reduction reaction method. An appropriate molar ratio between Au and Ag was proved to be a key factor influencing the SERS performance including the enhancement factor (EF) and selectivity for ampicillin determination. Many SERS hotspot areas can be explored along the thread and between the intertwined fiber using two-dimensional (2D) Raman mapping measurement. This substrate provides less spot-to-spot and sample-to-sample signal variation with low relative standard deviation (%RSD) values of 5.69, and 4.73%, respectively. Using the optimized Au–Ag alloy fabric as a SERS substrate, label-free ampicillin detection is demonstrated with a limit of detection (LOD) of 1.3 μM. To study the feasibility of this developed SERS substrate, detection of ampicillin spiked in natural raw water was selected for real sample analysis. Our SERS substrate can detect ampicillin with a recovery rate of 96 to 110%. With integration of Au–Ag alloy NPs and the complex structure of muslin fabric, this finding highlights a simple and cheap SERS substrate fabrication method for practical use without a sample preparation step.